2018
DOI: 10.1111/jth.14163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of compression in the acute phase of deep vein thrombosis

Abstract: IDEAL DVT study ClinicalTrials.gov number, NCT01429714.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…[39][40][41][67][68][69] There are no data suggesting that compression of veins filled with clots may lead to an increased risk of PE or post-thrombotic syndrome (PTS). 39,41,63,64,70,71 Recommendation 18. We recommend considering that, in contrast to previous concepts, compression is not contraindicated in acute thrombotic events, but results in favourable clinical outcomes when applied with caution.…”
Section: Deep and Superficial Vein Thrombosismentioning
confidence: 99%
“…[39][40][41][67][68][69] There are no data suggesting that compression of veins filled with clots may lead to an increased risk of PE or post-thrombotic syndrome (PTS). 39,41,63,64,70,71 Recommendation 18. We recommend considering that, in contrast to previous concepts, compression is not contraindicated in acute thrombotic events, but results in favourable clinical outcomes when applied with caution.…”
Section: Deep and Superficial Vein Thrombosismentioning
confidence: 99%
“…The effectiveness of compression therapy with good adherence as prophylaxis against PTS was shown again in the recently published OCTAVIA and IDEAL studies [32,33]. A sub-study of the IDEAL study also showed that starting compression therapy immediately rather than after 2 weeks led to significantly lower objective PTS parameters in the Villalta score [34].…”
Section: Prophylaxis Of Ptsmentioning
confidence: 86%
“…The OCTAVIA and IDEAL studies have recently confirmed that compression therapy with good adherence can significantly reduce the incidence of PTS [32,33]. The latest outcomes from the IDEAL study have also shown a reduction in the incidence of PTS when compression therapy is started immediately compared to delayed start [34]. In view of the above, the following is recommended:…”
Section: Indications For Medical Compression Therapy Recommendation 28mentioning
confidence: 99%
See 1 more Smart Citation
“…showed that immediate start of compression can significantly reduce the objective parameters of PTS using the Villalta scale after 3 months compared to delayed start of compression. 29 , 30…”
Section: Discussionmentioning
confidence: 99%